RESEARCH STATUS OF BIRD HELMINTHS IN UZBEKISTAN: https://doi.org/10.5281/zenodo.14227074 - Azbergenov , E.B.; Sarsenbaev , I.E.; Dilmanova , A.I. (International scientific and practical conference, 2024)
Introduction. Today, as a result of the regular increase in the population in the world, their demand for food, products and daily needs are also increasing. Measures such as quality and adequate feeding of poultry, strict adherence to veterinary and sanitary rules are the main factors in the performance of these tasks. Poultry occupy one of the important places in human life, since the diet of people, along with ensuring the need for meat and eggs, receives valuable feathers for industry, serves as the main sources in the preparation of local fertilizers for agriculture.